(untitled) (Tikrit Journal For Political Science, 2023)
The United States of America faces many internal threats and challenges, and terrorism is one of the most significant challenges and threats. The years following the attacks of (September 11, 2001) witnessed a substantial decrease in the rate of external (foreign) terrorism in the United States, at a time when domestic terrorism witnessed an apparent rise at unprecedented rates in the last two decades. There are four main categories of ideologies in the United States of America: the far right, the far left, religious extremism, and ethnic extremism. The far right is the first and most significant challenge and threat to the United States, as the operations and attacks of this wing have increased rapidly in terms of quality and quantity. Within this wing, there are many movements, and white extremists and anti-government extremists are considered the most critical movements. It is a statistical study that tries to shed light on domestic terrorism in the United States of America after the 11 September 2001 attacks by collecting data from American formal and informal institutions. The study utilizes the quantitative approach as a tool for analyzing these data.